Air Pollution : Evidence from the Gulf Environmental Partnership and Action Program - Naber, Helena (World Bank, Washington, DC, 2016)
This note is the first in the Gulf Cooperation Council (GCC) knowledge notes aimed to promote debate, discussion, and dissemination of knowledge for the most pertinent development questions the GCC region faces. It is based on the pollution load assessment reports for Bahrain, Kuwait, and Qatar prepared as part of the Gulf Environmental Partnership and Action Program national activities led by Helena Naber and Samia Al-Duaij.